Post a New Question


posted by .

Suppose (x^2)*(e^(-2y))= ln(xy)
Find dy/dx by implicit differentiation.

  • Math/Calculus. -

    2x(e^(-2y) ) + x^2(e^(-2y) )(-2dy/dx)= 1/(xy) (xdy/dx + y)

    2x e^(-2y) -2y x^2 e^(-2y) = (1/y) dy/dx + 1/x

    2x e^(-2y) - 1/x = dy/dx (1/y + 2x^2 e(-2y) )

    dy/dx = ( 2x e^(-2y) - 1/x ) / ((1/y + 2x^2 e(-2y)) )

    still pretty messy looking, I don't know how far you have to take it.

    Also, you better check my work. It is always harder to just type it here, rather than do it on paper.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question